The effects of emotional distress on attentional bias toward cigarette warnings according to smokers' anxiety levels - Jung, Younji; Hwang, Jang-Sun; Lee, Jang-Han (Frontiers in Psychology, 2024)
Anxiety is related with the substance use, including cigarette smoking. Avoidance is one of the strategies smokers with anxiety adopt to manage negative affect, which can be contradictory to a strategy of cigarette warnings that is used to induce negative affect to change smoking behaviors. Therefore, this study examined whether smokers’ anxiety levels decrease their attentional biases toward cigarette warnings, especially in response to emotional distress. High-anxiety(n=60) and low-anxiety(n=60) smokers were randomly assigned to either a stress condition that utilized the PASAT-C task(Paced Auditory Serial Addition Task-Computer version) or a controlled condition. With the eye-tracking task that involved viewing 8 visual stimuli of cigarette packs composed of warnings and brandings, time to first fixation and fixation duration to warnings compared to brandings were measured both pre and post conditions. The results revealed that high-anxiety smokers detected warnings faster after stress conditions while low-anxiety smokers showed the consistent time to first fixation on warnings. In terms of fixation durations, high-anxiety smokers showed hypervigilance towards warnings that are considered to be a threat, but low-anxiety smokers showed avoidance under stress conditions, particularly towards social-focused warnings. These results indicate that high-anxiety smokers are more vulnerable to emotional distress and have an attentional bias towards fear appeals. Despite hypervigilance, they had greater psychological reactance towards warnings that the conflict between avoidance and hypervigilance might have contributed to, so the effectiveness of fear appeals may be limited regardless of the increased fixation duration.